RETRACTED: Environmental responsibility as an element of legal culture of the population - Milova Irina; Oskin Egor (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001